Quinones Distribution of Teak Wood Grown in Community Forest - Ganis Lukmandaru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
Quinones and their derivatives are the main causes on the natural termite resistance in teak wood. By using different termite test methods, the previous paper in this series reported on the termite resistance of teak trees of juvenile ages (8- and 22-year old trees). In this study, the radial distribution of quinones (tectoquinone, lapachol, desoxylapachol and its isomer) and squalene in the different extracting solvents (n- hexane, ethyl acetate, and methanol) were analyzed by means of gas chromatography. Appreciable tree to tree variations were observed in extractive component contents even in the same stand. Each solvent gave different tendencies in analysis of variance of component  contents.  Signiﬁcant  diﬀerences  in  desoxylapachol  or  its  isomer,  and squalene content were found among the outer heartwood of 8- and 22-year old trees, as well as between the inner and outer parts of the heartwood. The highest correlation degree between extractive content and its components was measured in the tectoquinone content (r=-0.68). By using paper disc method, only modest correlations were observed between the mass loss and the content of isodesoxylapachol (r=-0.60) in the sapwood region whereas no significant corellations were measured in the heartwood region.